KEMAMPUAN MENULIS TEKS EKSPOSISI SISWA KELAS X - Deviana Nadilla; Haerun Ana; La Ode Adili (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2025)
This research aims to describe the expository writing skills of 10th-grade students at SMA Negeri 3 Kendari. This research falls under field research, conducted directly at SMA Negeri 3 Kendari, as the research object to collect data in accordance with the issues present in this study. The population in this research consists of all 10th-grade students at SMA Negeri 3 Kendari, totaling 240 students across 7 classes. The sample in this study consisted of 127 students with a margin of error of 10%. The sampling technique used was proportionate stratified random sampling, which involved ranking students' achievements from highest to lowest based on their daily test scores. The data collection technique used in this study was administering a test on writing expository texts. The research results show that out of 127 respondents, there were 56 (44.09%) students categorized as capable and 71 (55.90%) students categorized as not yet capable in writing expository texts. Classically, it can be categorized as not capable because it reached 44.09%, which does not exceed the established classical achievement criterion of 85%. Keywords: ability, writing, exposition.